Framework of Outsourcing in Indian DPSUs for Avionics ToT Projects and Statistical Analysis of its Operational Issue - Lakshman Singh; Alpana Srivastava (International Journal of Supply Chain Management, 2018)
Outsourcing in become one of the strategic tool for competitive economic growth of Avionics DPSUs in present global aerospace industry. In this paper author define the need of outsourcing in DPSUs, its structure and activity flow diagram. The research formalized the main reason for failure of outsourcing in Indian DPSUs using statistical analysis (Cronbach's Alpha technique )and developed model for outsourcing in Indian DPSUs for avionics Transfer of Technology project. Analytical finding of this research paper point out the need of vendor development for outsourcing as major issue for DPSUs and it become one of the responsibility for DPSUs to cater the criticality of Avionics TOT project. Finally paper concluded with the vendor development model criteria for vendor rating for outsourcing activity for Avionics TOT project.